Perilaku Konsumsi Komunitas Pengajian Al-Ikhlas Rungkut Surabaya - Elsha Sophia; Muhammad Nafik HR (Universitas Airlangga, 2014)
The main purpose of these research is to get the information about recitation's affection on the consumption behavior of Al-Ikhlas Rungkut Surabaya recitation community.This research use qualitative case study explanatory method. Data collection was done by interviewing, observating, and documentating on the Al-Ikhlas Rungkut Surabaya recitation community.The result obtained is recitation activity have an impact on consumption behavior undertaken by the majority of Al-Ikhlas Rungkut Surabaya recitation community with giving more attention to the appropriate Islamic consumption behavior, namely: 1) Halal and thayyib, 2) Not improvident and extravagant, and 3) balancing the consumption in the world and afterlife. Some members can be said to be improvident and extravagant because of their excessive consumption of goods and use the goods not according to their function, and eventually became redundant. It happens because they can not control their desire really well, although it does not harm them. Then, the behavior of consumption in order to fulfill the dharuriyyat, hajiyyat, and tahsiniyyat for the sake of religion, life, intelligence, descent, and property's maintenance have also been able to reach and fulfilled in a good way even though it is not perfect. REFERENCES Achmadi. 2005. Ideologi Pendidikan Islam. Yogyakarta : Pustaka Pelajar.Chaney, David. 2003. Lifestyles: Sebuah Pengantar Komprehensif. Yogyakarta. Jalasutra.Departemen Agama RI. 2011. Al-Qur'an Terjemahan. Bandung: DiponegoroHandayani, Endang Sih. 2009. Motivasi Ibuibu Rumah Tangga Mengikuti Pengajian Muslimat NU di Ranting Troso Kec. Karanganom Kab. Klaten. Yogyakarta. Universitas Islam Negeri Sunan Kalijaga Yogyakarta. (Online). http://digilib.uin-suka.ac.id (diakses 13 November 2013, jam 23.00).Hidayat, Mohammad. 2010. An Introduction to The Sharia Economic (Pengantar Ekonomi Syariah). Jakarta : Zikrul.Karim, Adiwarman A. 2007. Ekonomi Mikro Islami. Jakarta: PT Raja Grafindo.Langgulung, Hasan. 1986. Manusia dan Pendidikan. Jakarta: Al Husna.Mannan, Mohammad Abdul. 1996. Financing Development in Islam. Jeddah : IRTI.Muflih, Muhammad. 2006. Perliaku Konsumen dalam Perspektif Ilmu Ekonomi Islam. Jakarta: PT. Grafindo Persada.Nafik, Muhammad. 2009. Ekonomi ZISWAQ. Surabaya: IFDI. Ramayulis. 1994. Ilmu Pendidikan Islam. Jakarta: Kalam Mulia.Sukadi, Hananda Dwi. 2011. Pemahaman Perilaku Konsumsi Islam Sumber Daya Insani Departemen Ekonomi Syariah Universitas Airlangga. Surabaya: Universitas Airlangga. (Skripsi Tidak Diterbitkan).Sugiyono. 2011. Metode Penelitian Pendidikan: Pendekatan Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.Supranto, J. dan Nandan Limakrisna. 2007. Perilaku Konsumen dan Strategi Pemasaran untuk Memenangkan Persaingan Bisnis. Edisi Pertama. Jakarta: Mitra Wacana Media.